Cardiorespiratory fitness and the incidence of coronary surgery and postoperative mortality: the HUNT study. (12th March 2022) - Smenes, Benedikte Therese; Nes, Bjarne Martens; Letnes, Jon Magne; Slagsvold, Katrine Hordnes; Wisløff, Ulrik; Wahba, Alexander
Abstract: OBJECTIVES: Low physical activity and cardiorespiratory fitness are known risk factors for coronary artery disease, but how they affect the risk of undergoing coronary artery bypass graft surgery is not established. We explored how physical activity and estimated cardiorespiratory fitness affect the risk of coronary surgery and postoperative outcome. METHODS: Participants with no history of coronary disease from the second wave of the Trøndelag Health Study (HUNT2) were cross-linked with the local heart surgery register and the Norwegian Cause of Death Registry. Cardiorespiratory fitness was estimated by a previously developed algorithm using clinical and self-reported information. Fine-Gray competing risk analyses were used to calculate the risk of undergoing isolated coronary surgery across physical activity groups and estimated cardiorespiratory fitness (mL/kg/min) as quintiles and per 1 metabolic equivalent of task (MET) (3.5 mL/kg/min). RESULTS: We included 45, 491 participants. The mean population age was 46.0 [standard deviation (SD) 15.8] years, and the mean estimated fitness was 41.3 (SD 8.9) mL/kg/min. A total of 672 (1.5%) participants underwent coronary surgery during the follow-up period. The risk of undergoing isolated coronary surgery was 26% [95% confidence interval (CI) 3–44] lower for those classified as highly active compared to those classified as least active. Further, an 11% (95% CI 6–15) lower risk per 1-MET (3.5 mL/kg/min) of higher fitness. Finally, we observed a 15% (95% CI 5–23) lower mortality risk after surgery per 1-MET of higher fitness among those undergoing surgery. CONCLUSIONS: High levels of physical activity and high estimated fitness levels were inversely associated with the risk of developing coronary disease requiring surgery and overall mortality after surgery. Abstract : Coronary artery disease (CAD) is an important manifestation of cardiovascular disease (CVD), causing about one-third of all deaths in individuals older than 35 years [1].